2014
DOI: 10.1016/j.jsv.2014.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of uncertainty in the prediction of railway induced ground vibration due to the use of statistical track unevenness data

Abstract: Environmental vibrations due to railway traffic are predominantly due to dynamic axle loads caused by wheel and track unevenness and impact excitation by rail joints and wheel flats. Because of its irregular character, track unevenness is commonly processed statistically and represented by its power spectral density function or its root mean square (RMS) value in one-third octave bands. This statistical description does not uniquely define the track unevenness at a given site, however, and different track unev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…It was found that 96.45% of the results were within this confidence region, and that most of the results from the scoping model were higher in magnitude than those obtained from the detailed model. The uncertainty of the predictions from the scoping model were within a range between −3 dB to 11 dB and thus similar to the 5 dB -20 dB values found in previous research [43][44][45]. The sensitivity analysis showed that soil material properties were a relevant parameter that could affect the accuracy of the vibration level prediction, due to the deviation shown in Figure 10.…”
Section: Remarks Of the Sensitivity Analysissupporting
confidence: 84%
“…It was found that 96.45% of the results were within this confidence region, and that most of the results from the scoping model were higher in magnitude than those obtained from the detailed model. The uncertainty of the predictions from the scoping model were within a range between −3 dB to 11 dB and thus similar to the 5 dB -20 dB values found in previous research [43][44][45]. The sensitivity analysis showed that soil material properties were a relevant parameter that could affect the accuracy of the vibration level prediction, due to the deviation shown in Figure 10.…”
Section: Remarks Of the Sensitivity Analysissupporting
confidence: 84%
“…A good agreement is found with differences mainly found between −4.8 dB to 5.6 dB. Therefore the accuracy is similar to the uncertainty range between 5 dB to 20 dB as found in previous research [54,64,65].…”
Section: Discussionsupporting
confidence: 90%
“…The following describes the evaluation of train-track interaction forces (Figure 1 step 2.2). Both quasi-static excitation and dynamic excitation due to random track unevenness are taken into account [54], and the dynamic contributions depend upon the rail displacementsũ r (k y , ω) obtained using Equation (12).…”
Section: 5d Fem Formulationmentioning
confidence: 99%
“…The model of a load moving along a periodic (varying in space variable) Faculty of Civil Engineering, Cracow University of Technology, Chair of Rail & Air Transport Infrastructure, Poland structure has been analyzed by, for example, Auersch (2015), Bogacz et al (1998), Croft et al (2009), Hussein and Hunt (2009), Lombaert et al (2014) and Shenga et al (2004).…”
Section: Introductionmentioning
confidence: 99%